Risk factors for first episode of accident encephal vascular brain at different altitude levels - Romero Cordova, Jose (2020)
Objective. To determine the risk factors for the first episode of cerebral cerebrovascular accident (CVA) in people living at different levels of altitude. Methods. An observational, cross-sectional and analytical study was carried out in two hospitals located at 150 meters above sea level and 3250 meters above sea level, between 2012 and 2018, the sample was selected according to inclusion and exclusion criteria. The diagnosis of stroke was determined by tomography and / or brain resonance. Results. 72 (100 %) patients were included, 40 (55,5 %) lived at 150 meters above sea level and 32 (44,5 %) at 3250 meters above sea level; the averages of ages were 64,3 + -13,9 and 71,6 + - 14,0 years respectively (p = 0.033). The most affected age group was between 70 and 79 years, the highest percentage in height (43,7 % vs 27,5 %). The most frequent risk factors for stroke at sea level were arterial hypertension (95,0 % vs 62,5 %), diabetes mellitus (47,5 % vs 3,1 %) and atrial fibrillation (15,0 % vs 0,0 %) compared to altitude. The low socioeconomic level (81,2 % vs 27,5 %), the female gender (75,0 % vs 42,5 %), having valve disease (6,2 % vs 2,5 %) and polycythemia (9,3 % vs 0,0 %) were more frequently associated with stroke in height. Conclusions. It is concluded that arterial hypertension is an important risk factor for the first episode of brain stroke both at sea level and at altitude. Diabetes and atrial fibrillation were at sea level and in altitude, the low socioeconomic level, polycythemia, and suffering from valve disease.